The Wiley handbook of personality assessment - 4 0 16; Kumar, Updesh; 5 (Chichester, West Sussex, UK ;;Malden, MA : John Wiley & Sons, 2016)
The Wiley Handbook of Personality Assessment presents the state-of-the-art in the field of personality assessment, providing a perspective on emerging trends and placing these in the context of recent research advances. Linking theory with practice, the volume delineates current developments in theoretical conceptualisations affecting personality assessment, and charts the way forward for potential applications of these emergent research insights. The handbook brings together an international group of distinguished contributors from 17 countries on five continents, to tackle key issues in personality assessment across a range of approaches and contexts. This multi-national authorship enhances the content by bringing critically important cross-cultural perspectives and diversity across the subject--
Title Page; Copyright Page; Contents; About the Editor; About the Contributors; Foreword; Preface; Section I Emerging Conceptual Trends; Chapter 1 Integrating Trait and Process Approaches to Personality: A Sketch of an Agenda; Individual Differences: The Five-Factor Model; Intrapsychic Structure and Personality Processes; Assessing Personality Traits and Processes; Acknowledgments; References; Chapter 2 Personality Assessment and Theory; Surface Traits and Causal Sources; Bridging the Operational-Latent Gap; The Multifacted Nature of Assessment; The Cronbachian Perspective;Implications for Real World Personality AssessmentThe Way Forward?; Concluding Thoughts; References; Chapter 3 Situational Perception: Its Theoretical Foundation, Assessment, and Links to Personality; Lewin's Equation and the Person-Situation Debate; The Objective and Subjective Approaches; Two Situational Taxonomies; DIAMONDS and S5; Theories of Person-Situation Interaction; The Way Forward; Conclusion; References; Chapter 4 Temperamental Components of the Developing Personality; Phase II: Adding Temperament CBQ Content to the Hampton Child Personality Scales;Phase III: A Combined Measure of Child Temperament and Personality -- The CTPQOverarching Discussion; Acknowledgments; References; Chapter 5 Integrity Tests: A Review of Alternate Conceptualizations and Some Measurement and Practical Issues; Mapping Integrity Test Scores in the Personality Trait Space; Assessing the Empirical Evidence for Integrity Tests: Some Measurement and Practical Issues; Conclusions; References; Chapter 6 Network Analysis: A New Way to Think about Personality; Introduction to Network Analysis; Networks in Personality Psychology; Network Analysis of a Lexical Data-set;ConclusionsAcknowledgments; References; Chapter 7 Theory and Measurement of Trait Emotional Intelligence; What is Trait Emotional Intelligence?; Location of Trait EI in Personality Factor Space; Measures of Trait Emotional Intelligence; Incremental Validity of Trait Emotional Intelligence; Summary; Conclusion; References; Chapter 8 Beyond IQ and EQ: The Bar-On Multifactor Model of Performance; The Multifactor Measure of Performance$1!"(B; Why Create this Conceptual and Psychometric Model of Performance?; The Method Applied in Developing the Bar-On Model;The Potential Applicability and Importance of this ModelConcluding Comments; References; Chapter 9 Measuring the Dark Side of Personality; The Dark Triad of Personality; Comprehensive Dark Triad Measurement; Current and Future Directions; Conclusion; References; Chapter 10 Diversity and Assessment; Background and History of Multicultural Personality Assessment; Differential Norms; Cultural Validity of the Construct; Cultural Idioms of Distress and Reporting and Response Style; Cultural and Technical Context of the Testing Process; Culturally Informed Responses to Feedback; Conclusions
Includes index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: 2 -- 0; 6; Personality assessment.;PSYCHOLOGY / Personality.;Personality assessment; 20; Electronic books. -- 2